Identification of Leishmania species by next generation sequencing of hsp70 gene. (February 2022) - Maia de Souza, Regina; Ruedas Martins, Roberta Cristina; Moyses Franco, Lucas Augusto; Tuon, Felipe Francisco; de Oliveira Junior, Isael Gomes; Maia da Silva, Camila Alves; Imamura, Rui; Amato, Valdir Sabbaga
Abstract: Leishmaniasis is a major public health problem worldwide. Although next generation sequencing technology has been widely used in the diagnosis of infectious diseases, it has been scarcely applied in identification of Leishmania species. The aim of this study was to compare the efficiency of MinION™ nanopore sequencing and polymerase chain reaction restriction fragment length polymorphism in identifying Leishmania species. Our results showed that the MinION™ sequencer was able to discriminate reference strains and clinical samples with high sensitivity in a cost and time effective manner without the prior need for culture. Highlights: The identification of Leishmania species is essential to assist in the proper treatment. We use the latest generation sequencing for identification of Leishmania species. In this study we used the third generation MinION sequencer for the first time. MinION sequencer was able to discriminate reference strains and clinical samples with high sensitivity.